2010
DOI: 10.1159/000322307
|View full text |Cite
|
Sign up to set email alerts
|

The Histopathology of Revision Cochlear Implantation

Abstract: The current study evaluates histopathologic changes in the temporal bones of 4 human subjects who underwent revision cochlear implantation. Specimens were removed at autopsy, fixed and prepared for histological study by standard techniques. Specimens were serially sectioned, reconstructed by two-dimensional methods, and the tracks of the initial and revision cochlear-implant electrodes identified. The tracks were of three types: a ‘common track’ (shared by the reimplantation electrode and initial electrode), ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
9
0
3
Order By: Relevance
“…In cases with multiple surgeries, initial trauma was most likely due to the first implantation, as we have not seen evidence of damage from removal of an electrode. There is some conflicting evidence regarding the status of the sheath that surrounds an implant electrode after removal and reimplantation (17, 18). In this study, attention was paid in each multiple surgery case to determine whether a new electrode track was present.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with multiple surgeries, initial trauma was most likely due to the first implantation, as we have not seen evidence of damage from removal of an electrode. There is some conflicting evidence regarding the status of the sheath that surrounds an implant electrode after removal and reimplantation (17, 18). In this study, attention was paid in each multiple surgery case to determine whether a new electrode track was present.…”
Section: Discussionmentioning
confidence: 99%
“…Chute has insisted that both the level of cochlear neoosteogenesis and the electrode insertion depth might affect the postoperative hearing rehabilitation (24). On the contrary, evaluation of the histopathology of temporal bones of 4 human subjects who underwent revision CI revealed that a newly inserted electrode can make a new route in the cochlear duct as a common track or 2 tracks according to its pathology (21). They concluded that the electrode insertion depth at revision CI is not limited by the depth of insertion of the initial implant.…”
Section: Discussionmentioning
confidence: 99%
“…38 Finally, it disrupts the architecture of the organ of Corti and provokes subsequent hair cell and neuronal loss, further compromising the maintenance of residual hearing. 39 The development of cochlear fibrosis can be as- Fibrotic scar formation after cochlear implantation. Acute inflammatory reaction is triggered by insertion trauma that induces recruitment of inflammatory cells such as macrophages or lymphocytes to site, thus promoting elimination of cellular debris and secretion of cytokines and growth factors.…”
Section: Molecular Pathways Involved In Hearing Loss After Cochlear Imentioning
confidence: 99%